2005
DOI: 10.1128/jmbe.v6.78
|View full text |Cite
|
Sign up to set email alerts
|

A "Hybrid" Bacteriology Course: The Professor's Design and Expectations; The Students' Performance and Assessment

Abstract: A basic bacteriology course was offered in two successive academic years, first in a conventional format and subsequently as a "hybrid" course. The latter combined (i) online presentation of content, (ii) an emphasis on online resources , (iii) thrice-weekly, face-to-face conversations to advance understanding, and (iv) frequent student postings on an electronic discussion board. We compared the two courses through statistical analysis of student performances on the final examinations and the course overall an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…Furthermore, online learning may include activities among learners, links to resources and downloadable text materials, online quizzes, and electronic submissions of assignments (Dabbagh & Bannan-Ritland, 2005). The use of online forums to promote active learning becomes a valuable experience because students are allowed to respond in thoughtful ways to questions and share ideas through discussions which stimulate their critical thinking (Krawiec, Salter, & Kay, 2005;Williams, 2006). Starkie (2007) validates that learning merged with innovations and collaborations bring out upheld, practical, learning surroundings.…”
mentioning
confidence: 99%
“…Furthermore, online learning may include activities among learners, links to resources and downloadable text materials, online quizzes, and electronic submissions of assignments (Dabbagh & Bannan-Ritland, 2005). The use of online forums to promote active learning becomes a valuable experience because students are allowed to respond in thoughtful ways to questions and share ideas through discussions which stimulate their critical thinking (Krawiec, Salter, & Kay, 2005;Williams, 2006). Starkie (2007) validates that learning merged with innovations and collaborations bring out upheld, practical, learning surroundings.…”
mentioning
confidence: 99%
“…Although online courses can provide an effective method of instruction, the COVID-19 pandemic resulted in the need for “emergency remote teaching” ( 13 , 21 ). Many instructors simply did not have enough preparation, time, or training to develop well-designed online courses.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that well-designed online or hybrid undergraduate biology courses can be as effective as traditional face-to-face courses (6). While most of these studies examined student performance in nonmajors or introductory biology courses (7)(8)(9), studies have also reported equivalent online versus face-to-face learning outcomes among students in more advanced biology courses, including microbiology (10)(11)(12)(13)(14)(15). However, it should also be noted that another study found that students in a hybrid microbiology course performed less well than their counterparts in a face-to-face learning environment (16).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, successfully transitioning from the traditional classroom presents challenges regarding how to properly deliver course information in a web-based format. Some students may perceive a diminished level of interaction with the instructor in an online course (6,10) or that online course modules require too great of a work load (6). Faculty may also be concerned with the time commitment associated with an online course (7).…”
mentioning
confidence: 99%